Comparison of bone mineral density of runners with inactive males: A cross-sectional 4HAIE study - Krajcigr, Miroslav; Kutáč, Petr; Elavsky, Steriani; Jandačka, Daniel; Zimmermann, Matthew (PloS one, 2024)
The purpose of the study was to determine whether running is associated with greater bone mineral density (BMD) by comparing the BMD of regularly active male runners (AR) with inactive nonrunner male controls (INC). This cross-sectional study recruited 327 male AR and 212 male INC (aged 18-65) via a stratified recruitment strategy. BMD of the whole body (WB) and partial segments (spine, lumbar spine (LS), leg, hip, femoral neck (FN), and arm for each side) were measured by dual-energy x-ray absorptiometry (DXA) and lower leg dominance (dominant-D/nondominant-ND) was established by functional testing. An ANCOVA was used to compare AR and INC. The AR had greater BMD for all segments of the lower limb (p<0.05), but similar BMD for all segments of the upper limb (p>0.05) compared with INC. Based on the pairwise comparison of age groups, AR had greater BMD of the ND leg in every age group compared with INC (p<0.05). AR had grater BMD of the D leg in every age group except for (26-35 and 56-65) compare with INC (p<0.05). In the youngest age group (18-25), AR had greater BMD in every measured part of lower extremities (legs, hips, femoral necks) compared with INC (p<0.05). In the 46-55 age group AR had greater BMD than INC (p < 0.05) only in the WB, D Leg, D neck, and ND leg. In the 56-65 age group AR had greater BMD than INC (p<0.05) only in the ND leg. Overall, AR had greater BMD compared with INC in all examined sites except for the upper limbs, supporting the notion that running may positively affect bone parameters. However, the benefits differ in the skeletal sites specifically, as the legs had the highest BMD difference between AR and INC. Moreover, the increase in BMD from running decreased with age.
Keywords: Young Adult; krček femuru; Cross-Sectional Studies; Male; absorpční fotometrie; mladý dospělý; Adolescent; Adult; Aged; dospělí; mužské pohlaví; senioři; lidé středního věku; Femur Neck; mladiství; běh; lidé; Humans; Lumbar Vertebrae; kostní denzita; průřezové studie; Bone Density; Running; bederní obratle; Absorptiometry, Photon; Middle Aged